On a class of diagonal operators in the spaces of analytic functions and its application - Linchuk, Yu. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
Diagonal operators induced by the Taylor coefficients of hypergeometric functions and some properties of such operators in the spaces of functions analytic in arbitrary domains are investigated. The results are applied to study properties of the generalized Dunkl operator.